Pengaruh Struktur Modal dan Kinerja Keuangan terhadap Nilai Perusahaan Studi Empiris pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di BEI Periode 2019-2023 - Andhika Indah Pratiwi; Heikal Muhammad Zakaria (Peneliti.net, 2026)
This research investigates the effect of capital structure and financial performance on firm value, focusing on manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. Capital structure is measured using the Debt to Equity Ratio (DER), while financial performance is assessed through Return on Equity (ROE). Firm value is represented by the Price to Book Value (PBV), which reflects how the market values a firm relative to its book value. A quantitative research method is used, employing secondary data obtained from company financial statements and stock market data. This study aims to determine whether DER and ROE, both partially and simultaneously, have a significant effect on firm value. The results are expected to provide meaningful insights into the relationship between funding decisions, profitability, and market valuation. The findings could serve as a valuable reference for management in optimizing financial strategies, for investors in evaluating stock potential, and for policymakers in enhancing the competitiveness of the food and beverage industry. This study also aims to enrich the existing literature on corporate finance by exploring empirical patterns in one of Indonesia's most dynamic manufacturing sub-sectors.